Pertarungan Syariah di Ruang Wacana: Analisis Kritis Pandangan Keagamaan pada Tempo dan Suara Hidayatullah - Anshori, Dadang S. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This paper aims to describe the different discourses on syariah practices as presented in the mass media. The method used in this study is a qualitative design based on Fowler’s critical discourse analysis. The data sources consist of the language used to discuss syariah practices in Tempo magazine and Suara Hidayatullah. Some important findings from Tempo magazine include words such as discriminative, unconstitutional, authoritarianism, collision, enticing Islam constituent, minority group, not applicable, children’s rights protection, traumatic, stigma, violent act, and repressive. Meanwhile, the word choices found in Suara Hidayatullah include terror, criminal acts, careless conclusion, cynical, simplistic, unprofessional, defamation, and anti-Islam. Based on these lexical choices, Tempo and Suara Hidayatullah express both explicit and implicit attitudes: the former presents an anti-syariah stance rooted in pluralist democracy, whereas the latter adopts a pro-syariah stance based on Islamic ideology.